Histochemical and ultrastructural analysis of hepatic glycogen and collagen fibers in alloxan-induced diabetic rats submitted to long-term physical training - Remedio, R. N. [UNESP]; Barbosa, R. A. [UNESP]; Castellar, A. [UNESP]; Gomes, R. J.; Caetano, F. H. [UNESP] (Elsevier, 2011)
Alterations in liver functions are common among diabetic patients, and many symptoms in the liver have been reported, including changes in glycogen stores and in the amount of collagen fibers. The practice of physical training and its morphological effects in this organ, however, are scarcely studied. In order to observe the morphological effects of alloxan-induced diabetes and the alterations arising from the practice of long-term chronic physical training in the liver, samples were collected and processed, and then analyzed by means of the histochemical techniques Periodic Acid-Schiff and Picrosirius-Hematoxylin, and ultrastructural cytochemical test of Afzelius. Through evaluation of the tissue, it was observed a drastic reduction in hepatic glycogen stores of sedentary diabetics, recovered in trained diabetic rats. Furthermore, it was detected a decrease in the content of perisinusoidal collagen fibers in the diabetic liver, also recovered due to the development of a training protocol. On ultrastructural level, cytochemical analysis confirmed the loss of glycogen and the recovery obtained by training. In conclusion, the practice of a long-term chronic physical training protocol may be considered an important assistant in the treatment of diabetes, mitigating the occurrence of possible damages to liver tissue. © 2011 Elsevier Ltd.
Keywords: Diabetes; Histochemistry; Liver; Physical training; Ultrastructure; collagen fiber; glycogen; aerobic exercise; animal experiment; animal model; animal tissue; controlled study; cytochemistry; diabetes mellitus; glycogen analysis; glycogen liver level; histochemistry; liver fibrosis; liver sinusoid; long term care; male; nonhuman; periodic acid Schiff stain; rat; training; ultrastructure; Animals; Blood Glucose; Collagen; Diabetes Mellitus, Experimental; Extracellular Matrix; Insulin; Insulin-Like Growth Factor I; Liver Glycogen; Male; Physical Conditioning, Animal; Rats; Rats, Wistar; Rattus